Representing Multicultural Semarang through Gambang Semarang’s Narrative - Rona Cita Azizah; Susanna Edelweiss; Angelika Riyandari (Soegijapranata Catholic University, 2018)
Dance is usually perceived as a structured movement done by a person or more and accompanied by music and in some cases songs. The attention on physical movement often neglects the narrative which may exist behind a dance. Dances often have stories which frame the sequence of movements done by the dancers. The stories in a dance have elements of literature such as theme, plot, characters, and setting. This paper which is part of an on-going research on Semarang traditional dance discusses the story told through the movements and costume of Gambang Semarang dance. Gambang Semarang is traditional performing arts from Semarang which originally consists of music, vocal, dance, and comedy. Gambang Semarang dance was a small part of Gambang Semarang performance, but it is often performed separately from the complete performance now. The dance is commonly accompanied by Gambang Semarang music which combines Javanese music instruments, gamelan, and Chinese music instruments. In some occasions, songs such as Gambang Semarang and Gado-Gado Semarang are presented along with the music. Gambang Semarang dance itself is often considered as Semarang’s identity as the dance tries to embrace the multicultural society of Semarang which are Javanese, Chinese, and Arabs through the dance movements and the costume worn by the dancer. Data were collected through interviews with key informants. The results of the interviews then were analyzed to find out the stories represented by Gambang Semarang. The findings show that dance movements and costumes of Gambang Semarang indeed represent multicultural Semarang.